2011
DOI: 10.4137/cmo.s5733
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Metastatic Mucoepidermoid Carcinoma Complicated by Resistant Hypercalcemia

Abstract: Tumors of salivary glands are uncommon and comprise of about 2%–4% of all head and neck tumors. About 75%–80% of these tumors are benign and include pleomorphic adenoma, monomorphic adenoma, oncocytoma, and papillary cystadenoma lymphomatosum. Mucoepidermoid carcinoma is the most common malignant tumor of salivary glands, representing 5–10% of all salivary gland tumors. Although known to be metastatic to local lymph nodes, distant metastases are rare (especially, with low and intermediate grade tumors). Histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…To the best of our knowledge, there is no case report of parotid gland oncocytoma-induced hypercalcemia in the literature. However, Popalzai et al [11] reported a case of metastatic mucoepidermoid carcinoma-induced hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is no case report of parotid gland oncocytoma-induced hypercalcemia in the literature. However, Popalzai et al [11] reported a case of metastatic mucoepidermoid carcinoma-induced hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
“…MEC commonly presents as a painless swelling with pressure; however, symptoms vary with tumor size and site [ 7 ]. High-grade tumors tend to metastasize to local lymph nodes, but rarely distant metastases can also occur [ 8 ]. However, even low-grade MEC has also been shown to metastasize [ 9 ].…”
Section: Introductionmentioning
confidence: 99%